Effects of the Traditional Chinese Medicine in the different acting styles on glucocorticoid receptor (GR) in brain cytosol and glucocorticoid receptor (GR) in the thymus during long-term progressive load training - Chang, B. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim was to to study the mechanism of immunosuppression and the effects of the traditional Chinese medicine in the different acting styles on GR in brain cytosol and GR in the thymus during long time progressive load training.